INTEGRASI PENILAIAN PORTOFOLIO DALAM PEMBELAJARAN PAI DI MADRASAH - Syamsuddin, - -; Asy’ariy, - - (Al Tadib : Jurnal Ilmu Pendidikan, 2015)
This article is aimed at discussing the integrationof portfolio assessment in learning PAI in Madrasah.Integration of portfolio assessment in learning PAI hasmajor advantages, namely the involvement of learnersactively and creatively in the overall process of learningand assessment. With measurable planning, learning is notout of context, and oriented towards sustainable progress,students are positioned as subjects rather than objects oflearning and teaching. Portfolio not only as a way ofassessment but could serve as a learning strategy. With aportfolio of all aspects of the domain capable of optimallyexplored through the involvement of students in the wholeprocess of learning and assessmentKeywords: Portfolio assessment, Learning